Identification of Environmental Change in Bukit Kerang, Aceh Tamiang Regency Using Landsat Satellite Imagery - Simatupang, Sphinoza Lisnaria; Rahmatsyah, Rahmatsyah (Jurnal Ilmu Fisika, 2022)
Changes in land cover and temperature in Bukit Kerang have been investigated using Landsat satellite images. We used Landsat 5 TM Landsat satellite imagery in 1988, Landsat 7 ETM in 2000, and Landsat 8 OLI in 2020. The ENVI 4.7 and ArcGIS 10.3 software was used to perform radiometric corrections, image cropping, image classification, image reclassification, calculating area, and layouts. Changes in land cover and land area in 1988, 2000, and 2020 affected the surface temperature conditions in those three years. In 1988, the dominant land area of forest cover was 5,926.44 ha (1 ha = 104 m2), with the dominant temperature distribution of 17.2° C. In 2000, there was an increase in settlements by 25.56 ha and rice field area, which caused an increase in the temperature distribution of 19.7 – 25.4° C. In 2020, forest type land cover changes into plantations, fields, and settlements decreased by 3,731.91 ha, increasing temperature distribution of 20.6 – 21.8° C. Thus, there is a strong relationship between changes in land cover and change in surface temperature in Bukit Kerang area.